Penyajian Laporan Keuangan Entitas Berorientasi Nonlaba Berdasarkan ISAK 35 Di Gereja HKBP Pangaribuan - Sahala Purba; Deby Tobing; Hizkia Tambunan; Leni Siagian; Rejeki Elmawati (Yayasan Literasi Sains Indonesia, 2022)
The church as a non-profit oriented entity financially accepts donations from the congregation/ congregation to fund its ministry activities. Legitimacy theory can be used to explain the position of the church as an entity that has a social contract with the people, namely how the church in this case the church manager can provide services church that grows and maintains the faith and belief of the people through all its activities. Non-profit financial reporting is regulated by ISAK 35. Interested parties will be able to assess the church's financial performance with the implementation of ISAK 35. The HKBP Pangaribuan Church is the object of this research. interviews and observations were conducted to collect data. So far, the Pangaribuan HKBP Church has only made reports on cash in and cash out. This study aims to describe the financial statements of the HKBP Pangaribuan Church with financial reports based on ISAK 35 by using an auxiliary application, namely MS. Excel. In short, non-profit organizations are different from business entities. Although non-profit organizations do not focus on making profit, they still face financial problems because non-profit organizations have budgets, pay employees, pay bills, electricity and telephone and others. The church is a non-profit organization that is a place of worship for Christians. The church is also used as a place to study the Bible and of course to study religion.